Taming Nitrene Reactivity with Silver Catalysts - Vine, Logan E.; Zerull, Emily E.; Schomaker, Jennifer M. (Synlett, 2021)
Nitrene transfer (NT) is a convenient strategy to directly transform C–H bonds into more valuable C–N bonds and exciting advances have been made to improve selectivity. Our work in silver-based NT has shown the unique ability of this metal to enable tunable chemo-, site-, and stereoselective reactions using simple N-dentate ligand scaffolds. Manipulation of the coordination environment and noncovalent interactions around the silver center furnish unprecedented catalyst control in selective NT and provide insights for further improvements in the field.1 Introduction1.1 Strategies for Nitrene Transfer1.2 Brief Summary of Chemocatalyzed Nitrene Transfer1.3 Focus of this Account2 Challenges in Chemocatalyzed Nitrene Transfer2.1 Reactivity Challenges2.2 Selectivity Challenges2.3 Chemoselective Nitrene Transfer2.4 Site-Selective Nitrene Transfer2.5 Enantioselective Nitrene Transfer3 Summary and Perspective3.1 Future Opportunities and Challenges3.2 Conclusion
Keywords: silver; nitrene transfer; C–H functionalization; amination; amines; asymmetric